2016
DOI: 10.1016/j.rbmo.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Association of a promoter polymorphism in FSHR with ovarian reserve and response to ovarian stimulation in women undergoing assisted reproductive treatment

Abstract: Previous studies have suggested an association between a variant in the promoter region of the FSHR gene and diminished response to controlled ovarian hyperstimulation (COH) in women undergoing assisted reproduction. FSHR -29G>A was genotyped in 559 women undergoing their first cycle of COH for IVF/intracytoplasmic sperm injection (ICSI) using TaqMan allelic discrimination assay. Correlation and regression analysis was performed to assess the relationship between FSHR promoter genotypes and markers of ovarian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 19 publications
2
13
1
Order By: Relevance
“…Moreover, A/G-G/G was associated with higher AFC, lower basal FSH, lower 17β-estradiol and lower FORT in comparison with other genetic variants, supporting its positive predictive factor for the success of ovarian stimulation. The positive association between A/G-G/G and basal FSH contradicts the published studies which considered the different allelic combinations of c.2039 A>G and c.-29 G>A [4,28,31], where no correlation with basal FSH was found. The negative association with FORT could be explained by the selection of the antral follicles with the greatest developmental potential.…”
Section: Discussioncontrasting
confidence: 78%
See 4 more Smart Citations
“…Moreover, A/G-G/G was associated with higher AFC, lower basal FSH, lower 17β-estradiol and lower FORT in comparison with other genetic variants, supporting its positive predictive factor for the success of ovarian stimulation. The positive association between A/G-G/G and basal FSH contradicts the published studies which considered the different allelic combinations of c.2039 A>G and c.-29 G>A [4,28,31], where no correlation with basal FSH was found. The negative association with FORT could be explained by the selection of the antral follicles with the greatest developmental potential.…”
Section: Discussioncontrasting
confidence: 78%
“…Specifically, Wunsch et al [4] have found no correlation of this polymorphism with ovarian reserve or ovarian response to stimulation. The same conclusion was reached very recently by Tohlob et al [28]. On the other hand, and with reference to the paper by Achrekar et al [29], patients with the A/A variant required a higher total dose of gonadotropins in order to reach significantly lower levels of estradiol on the day of hCG administration with a lower number of retrieved oocytes.…”
Section: Introductionsupporting
confidence: 75%
See 3 more Smart Citations